Efeito da fotobiomodulação na dor após tratamento endodôntico em sessão única de molares maxilares: um ensaio clínico randomizado duplo-cego - Machado, Gláucia Gonçales Abud (2024)
Introduction: The evidence regarding photobiomodulation (PBM) for postoperative pain reduction following endodontic instrumentation is classified as having low or very low certainty, highlighting the need for further studies. Systematic reviews emphasize the need for standardization of dental samples (for example, including only molars), dosimetric parameters, and the control of medication use. Additionally, longitudinal postoperative pain assessments over the 24-hour time course are critical, and studies should further explore these pain periods. This study evaluated the effect of PBM on pain following single-session endodontic instrumentation of maxillary molars at 4, 8, 12, and 24 hours. Methodology This double-blind, randomized controlled clinical trial was approved by the Research Ethics Committee (5.598.290) and registered on Clinical Trials (NCT06253767), initially recruited participants requiring endodontic treatment only in maxillary molars of both genders aged between 21 and 70 years, excluding certain health conditions, medication use, or complexities hindering single-session treatment. Fifty-eight maxillary molars treated endodontically in a single visit were randomly allocated into two groups: the PBM Group (n=29), which received conventional endodontic treatment combined with PBM (100mW, 333mW/cm2 and 9J distributed in 3 points near root apices), and the Control Group (n=29), which received conventional treatment with a PBM simulation. The primary outcome was spontaneous pain 24 hours after treatment. Secondary outcomes included pain reported at 4, 8, and 12 hours, pain during palpation and percussion at 24 hours, OHIP-14 analysis, and prevalence after treatment. Pain levels were assessed using the Visual Analog Scale (VAS). Statistical analyses included chi-square and Mann-Whitney tests using SPSS software version 29. The explained variance analysis (η²) was also calculated. Results: Ten participants were excluded: six for incorrect use of analgesics and four for not experiencing post-treatment pain in any of the outcomes assessed. Thus, 48 patients were analyzed. No differences were found between the groups in postoperative pain at 24, 4, 8, and 12 hours, nor during palpation and percussion (p>0.05), or in the OHIP-14 analysis. The pain frequencies ranged from 12.5% to 25% across groups at the 4h, 8h, 12h, and 24h intervals. Conclusion: No differences were found between the groups, suggesting that PBM does not influence post-treatment pain in maxillary molars during any of the evaluation periods under these experimental conditions.